Mexican education reform: elucidating dissenting teachers' resistance. Issue 1 (2nd January 2022) - Parra-Perez, Lizeth Guadalupe; Gloeckner, Gene W.; Valdés-Cuervo, Angel Alberto; Addo, Reuben; Harindranathan, Priya
ABSTRACT: Educational researchers need to pay more attention to understanding the perspectives of implementers as a means to preventing future implementation failures. In an attempt to elucidate the reasons for resistance to the implementation of the 2013 education reform in Mexico, qualitative methods were used to explore the lived experiences of dissenting teachers of the National Union of Education Workers (SNTE) over the cycle of policy in depth. This qualitative study analyzed the narratives of participants. The results revealed manifestations of power in four main categories: (1) agenda-setting imposition; (2) a policy formulation process led by social, economic, and political elites; (3) scientific legitimization; and (4) resistance to the implementation. Results showed that participants' resistance was primarily triggered by feeling that teachers' interests were excluded in the policymaking process. Therefore, in the future, democratization of the education policy-making process is a must within the Mexican context.